Impaired Clinical Efficacy of Aspirin in Hypoalbuminemic Patients With Diabetes Mellitus - Sciacqua, Angela; Andreozzi, Francesco; Succurro, Elena; Pastori, Daniele; Cammisotto, Vittoria; Armentaro, Giuseppe; Mannino, Gaia C.; Fiorentino, Teresa Vanessa; Pignatelli, Pasquale; Angiolillo, Dominick J.; Sesti, Giorgio; Violi, Francesco (Frontiers in Pharmacology, 2021)
Objective To investigate the impact of albumin levels on the aspirin efficacy, since albumin inhibits platelet aggregation (PA) by cyclooxygenase 1 irreversible acetylation that is less effective in patients with type 2 diabetes mellitus (T2DM). Patients and Methods A total of 612 aspirin (100 mg/day)-treated T2DM patients were followed-up for 54.4±7.3 months. The primary endpoint, a composite of cardiovascular death, myocardial infarction, ischemic stroke and coronary revascularization, were analysed according to baseline values of serum albumin (≥ or < 3.5 g/dL). Serum thromboxane (Tx)B2 was also measured. Results Overall, 250 (40.8%) patients had serum albumin < 3.5 g/dL; these patients were overweight and had higher values of fibrinogen (p=0.009), high sensitivity C-reactive protein (p=0.001) and fasting plasma glucose (p<0.0001) compared to those with albumin ≥3.5 g/dL. A total of 86 cardiovascular events were recorded during follow-up, 49 and 37 in patients with serum albumin < or ≥3.5 g/dL, respectively (p=0.001). At multivariable Cox regression analysis, serum albumin <3.5 g/dL (hazard ratio [HR] 1.887, 95% confidence interval [CI] 1.136-3.135, p=0.014), age (HR 1.552 for every 10 years, 95%CI 1.157-2.081, p=0.003), fasting plasma glucose (HR 1.063, 95%CI 1.022-1.105, p=0.002) and beta-blocker use (HR 0.440, 95%CI 0.270-0.717, p=0.001) were associated to cardiovascular events. Serum TxB2 levels (n=377) were 0.32±0.12 and 0.24± 0.12 ng/ml in patients with albumin